The APPROXIMATE SOLUTIONS OF MALARIA DISEASE TRANSMISSION MODEL: USING MUTI-STEP DIFFERENTIAL TRANSFORMATION METHOD (FUDMA JOURNAL OF SCIENCES, 2023)
In this paper, numerical solutions to the SPEIR-SEI Malaria disease model were obtained using the Multi-Step Differential Transformation Method (MS-DTM). MS-DTM is a semi-analytical method for solving a system of a non-linear differential equation where its exact solution is difficult to obtain. The analytical solution of MS-DTM was compared with the solution of Maple21’s in-built classical fourth-order Runge-Kutta method. The results demonstrate the reliability and efficiency of the method and the graphs show that the solutions from both methods agreed well with each other.
Keywords: Malaria disease; Fourth order Runge-Kutta method; Multi-Step Differential Transform Methods; Maple21; SPEIR-SEI